Structural Modifications in Predicative Constructions in Arabic Sentences: Advancement and Delay through Girgani Systems Theory - Hamid, GHOUIREG (Journal of Ecohumanism, 2026)
Arabic sentence construction is intrinsically built upon two pivotal elements: the predicate and the subject. These elements manifest as the nominal subject and predicate in nominal sentences, and as the verb alongside the actor or its equivalent in verbal sentences. Typically, a predefined sequence governs these components; however, this sequence can be modified for enhanced rhetorical effect. Such modifications, detailed by Abdul Qahir al-Jurjani, involve various adjustments like advancements and delays. These are not merely stylistic choices but are carefully implemented to preserve clarity and structural integrity, avoiding the need for rote memorization of sentence structure. By deviating from the conventional order, speakers can unveil deeper semantic layers and achieve specific lexical effects. This paper will explore these rhetorical strategies through a contemporary linguistic lens.